CONSULTATIVE BOARD ROLE OF COUNTRY (BPD) IN MONITORING IMPLEMENTATION OF GOVERNMENT IN THE COUNTRY BY ACT NUMBER 6 OF 2014 CONCERNING THE COUNTRY - Rifandy Ritonga; Indah Satria (International Conference On Law, Business and Governance (ICon-LBG), 2016)
The country is a unit of community that has boundaries. Authorized to regulate and manage the affairs of government, local community interests and customary rights recognized and respected in the governance system of the Republic of Indonesia. In exercising the authority to regulate and manage their own affairs and interests of local communities. Assigned both central and local government, there must be supervision. Supervising the implementation of the country administration is the most important reason why the Country Consultative Body (BPD) to be formed.